Population Density and Biological Studies of Two Cucucrbit Flies Species :Dacus ciliates Loew and Dacus frontalis Beecker (Diptera: Tephritidae) - Maysoon Ali Shawkit; Basam AL –Neamey; Fatma Hussian; Liqa Hady Edan; Abdel Razak Mahmood (Journal of Madenat Alelem University College, 2011)
Population density of cucurbit flies Dacus ciliates and Dacus frontalis were studied in Suwaira and Tuwaitha areas in addition to percentage of infestation by these two species on three varieties of vegetables: Cucumber, Snake Cucumber and Squash. Results showed that no significant differences in the number of eggs laid and percent of its hatching for the wild and laboratory strains mated separately for each species.